[Final accepted version, edited] Redefining genomic view of Clostridioides difficile through pangenome analysis and identification of drug targets from its core genome - Nikita Chordia Golchha; Anand Nighojkar; Sadhana Nighojkar (AboutScience Srl, 2022)
Introduction: Clostridioides difficile infection (CDI) is a leading cause of gastrointestinal infections and in the present day is a major concern for global health care system. The unavailability of specific antibiotics for CDI treatment and its emerging cases worldwide further broaden the challenge to control CDI. Methods: The availability of a large number of genome sequences for C. difficile and many bioinformatics tools for genome analysis provides the opportunity for in silico pangenomic analysis. In the present study, 97 strains of C. difficilewere used for pangenomic studies and characterized for their phylogenomic and functional analysis. Results: Pangenome analysis reveals open pangenome of C. difficile and high genetic diversity. Sequence and interactome analysis of 1,481 core genes was done and eight potent drug targets are identified. Three drug targets, namely, aminodeoxychorismate synthase (PabB), d-alanyl-d-alanine carboxypeptidase (DD-CPase) and undecaprenyl diphospho-muramoyl pentapeptide beta-N-acetylglucosaminyl transferase (MurG transferase), have been reported as drug targets for other human pathogens, and five targets, namely, bifunctional diguanylate cyclase/phosphodiesterase (cyclic-diGMP), sporulation transcription factor (Spo0A), histidinol-phosphate transaminase (HisC), 3-deoxy-7-phosphoheptulonate synthase (DAHP synthase) and c-di-GMP phosphodiesterase (PdcA), are novel. Conclusion: The suggested potent targets could act as broad-spectrum drug targets for C. difficile. However, further validation needs to be done before using them for lead compound discovery.